STRATEGI MANAJEMEN HUMAS DALAM PELAKSANAAN PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 DI SMPN 1 PRINGGARATA - Nurul Atika, M. Ary Irawan, dan Haromain (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2021)
This study aims at describing the public relations management strategy in the implementation of distance learning during the Covid-19 pandemic at State Junior High School 1 Pringgarata, such as planning, organizing, implementation, and monitoring strategy. This research uses a qualitative approach. The data collected using observation, interviews, and documentation. The results of this study shows that: (1) the PR strategies in distance learning planning are as follows: conducting general meetings in accordance with circular guidance, determining the best learning method both online and offline, and socializing to parents of students; (2) the strategies in organizing long distance learning, namely collaborating among vice-principals and related teachers, making learning schedules, and making study groups to facilitate the implementation of learning; (3) the strategies in implementing distance learning consist of online and offline learning, but there are obstacles in the implementation, namely, the students have different condition in the use of gadget, bandwidth issues in online learning, and the students absences in the offline learning; and (4) the strategies in monitoring distance learning are carried out through direct monitoring at the teaching and learning location in offline, as well as in online learning by appealing to parents to control their children during learning, and reinforcing health protocols by continuing to implement 3M.